Existence of Griffiths phase and unusual spin dynamics in double perovskite Tb2CoMnO6 - Anand K.; Alam M.; Pal A.; Singh P.; Kumari S.; Joshi A.G.; Das A.; Mohan A.; Chatterjee S. (My University, 2025)
The structural, electronic structure and magnetic properties of double pervoskite Tb2CoMnO6 have been investigated. Electronic structure analysis by X-ray Photoemission Spectroscopy Study (XPS) study reveals the presence of mixed oxidation state (Mn4+/Mn3+ and Co2+/Co3+) of B-site ions. Different interesting phenomena such as emergence of Griffith phase, appearance of Hopkinson like peak and also unusual slow relaxation are observed. It has been demonstrated that the presence of inherent anti-site disorder along with mixed valence states of B-site ions and Jahn-Teller active ions are the most important ingredients for the evolution of Griffith phase. Moreover, the presence of Hopkinson like peak has been attributed to the domain wall motion and the large anisotropy field. The further study yielded that the relaxation associated with this peak is unusually slow. © 2020